2005
DOI: 10.1093/eurheartj/ehi426
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the management of patients after heart valve surgery

Abstract: Approximately 50,000 valve replacement operations take place in Europe annually and almost as many valve repair procedures. Previous European guidelines on management of patients after valve surgery were last published in 1995 and were limited to recommendations about antithrombotic prophylaxis. American guidelines covering the broader topic of the investigation and treatment of patients with valve disease were published in 1998 but devoted relatively little space to post-surgical management. This document rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
163
0
29

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(196 citation statements)
references
References 70 publications
4
163
0
29
Order By: Relevance
“…13 While high-visibility studies 14 suggested that TEs were exceptional with optimal anticoagulation, TEs remain a major problem after mechanical MVR, 6 and their link to anticoagulation quality remains controversial. 7,10,14 -19 Many studies 3,7,9,10,18,20,21 have analyzed convenience samples of mechanical MVR, but incomplete or sparse anticoagulation data have been usual.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 While high-visibility studies 14 suggested that TEs were exceptional with optimal anticoagulation, TEs remain a major problem after mechanical MVR, 6 and their link to anticoagulation quality remains controversial. 7,10,14 -19 Many studies 3,7,9,10,18,20,21 have analyzed convenience samples of mechanical MVR, but incomplete or sparse anticoagulation data have been usual.…”
mentioning
confidence: 99%
“…22 Hence, clinical guidelines 2,13,22-24 acknowledge scant evidence supporting anticoagulation recommendations and are remarkably discrepant (European vs American guidelines) regarding the thrombogenicity of mechanical prostheses and the tailoring of the goals of anticoagulation to patient and prosthesis. 2,13,22,23 Therefore, we sought to evaluate the factors associated with TEs in patients who have undergone mechanical MVR in the population (not referral practice) with a complete record of all TEs and of the entire anticoagulation profile. We aimed at analyzing the link between TEs and the anticoagulation achieved and the prosthesis type.…”
mentioning
confidence: 99%
“…Recent recommendations advocate substituting warfarin after 35 weeks, because of the risk for intracranial haemorrhage of the child during delivery. 8,14 If there is no major bleeding after delivery, unfractionated heparin needs to be restarted four to six hours after delivery and oral anticoagulation can be given after 24 hours (target INR 2.5 to 3.5 in high-risk patients and 2.0 to 3.0 in low-risk patients.…”
Section: A B a Bmentioning
confidence: 99%
“…14 Monitoring lysis of the valve thrombosis with TEE is recommended to detect increasing and obstructing thrombi. 14 When patients present with severe heart failure, there is a need for emergent valve replacement. 15,16 When surgery is not available or no longer an option, thrombolysis should be considered.…”
Section: Management Of Valve Thrombosismentioning
confidence: 99%
“…Он также может служить причиной дисфункции кла-панного протеза, возникновения парапротезных фистул, а также быть источником опасных эмболий, что в боль-шинстве случаев требует хирургического лечения с репро-тезированием клапана [6,7].…”
unclassified